Trail of Mud: On Trauma and Ethics in Israeli Film and Literature - Gertz, Nurith; Hermoni, Gal (MiKAN, 2013)
The article discusses ethical issues involving “otherness” and victimhood in relation to certain traumas endemic to Israeli society. Several Israeli cinematic and literary texts (Waltz with Bashir, Winter Games, Hirbet Hize, and others) are shown to point back to a core trauma embedded in Zionist discourse—that of the Palestinian expulsion of 1948. As the texts under consideration show, understanding this and later traumas can serve as a basis for an ethical attitude which recognizes both the trauma of the other as a victim and the trauma of the self as a perpetrator.